The effect of firm and country characteristics on earnings management: Evidence from the hotel industry - Paiva, I.; Lourenço, I. (XXVI Jornadas Luso-Espanholas de Gestão Científica: Competitividade das Regiões Transfronteiriças, 2016)
This paper explores the determinants of firm and country characteristics in explaining the earnings management in a wide sample of listed firms from the tourism industry in 15 countries over 2007 – 2013. We focus on the level of discretionary accruals as a dimension of earnings management that is particularly responsive to firms’ financial statement incentives and examine the variables that are potentially associated with the earnings management in hotel firms. The results suggest that firm characteristics are the major determinant of earnings management in the hotel industry around the world. Additionally, our results demonstrated that star rating classification is the determinant of earnings management in high development countries. This paper aims to contribute to knowledge about the tourism industry by examining the determinants of earnings management across a large panel of firms and countries and by focusing on both the characteristics of the firm and its institutional environment.